Palynology of cretaceous amber deposits of the oriente basin-Ecuador and the eastern cordillera- Colombia - Castaño Cardona, Rafael Francisco (2023)
Several Cretaceous amber-bearing localities were recently discovered, including the Oriente Basinof Ecuador (Hollín Formation), and the Eastern Cordillera of Colombia (Une Formation at La Popamine). A palynological study of 48 samples was carried out to date them and assess their broadfloristic content. We date the Hollín Formation as spanning the late Aptian to the early Albian basedon the co-occurrence of Callialasporites trilobatus, Retitricolpites operculatus and Callialasporitesdampieri, among others. The sandstone lens containing amber from Une Formation at La Popa minewere dated as latest Aptian to early Cenomanian based upon the co-occurrence of Callialasporitesdampieri, Afropollis jardinus, Ischyosporites variegatus and Gnetaceaepollenites retangularis.The palynoflora is dominated by high spore diversity suggesting humid climate conditions in thenorthwestern margin of Gondwana.